A Sixty-Year Evolution of Biochemistry at McGill University - Johstone, Rose (Scientia Canadensis, 2003)
AbstractThe Department of Biochemistry at McGill University was inaugurated close to a century after the Medical School was founded. The roots of the Department, however, can be found at the very beginning of the Medical School in 1829. Because several of the founding faculty members of the Medical School were educated in Edinburgh, McGill's early medical program bore the imprint of the Edinburgh school-particularly in the importance placed on instruction in chemistry and on basic research. This survey of the development of a university department is structured on the succession of department chairs, and describes how the Department's scientific, pedagogical, and administrative activities were influenced by the particular abilities and dispositions of the individuals who were at the helm. It explains how the growth of external research institutes influenced the Department's evolution, and cites some of the noteworthy contributions of its members.